Implementation Of The Inclusion Of A Self-Protection Clause In The Production Of A Notarial Deed (Study At The Notary Office Of Dimitri Danang Sawitrawan, S.H., M.Kn.) - Verahardianti Putri, Zulfa (Universitas Islam Malang, 2024)
Abstract : Notaries have a very important role in making deeds, because notaries have been appointed by law to make these deeds. In carrying out the duties of his position, especially in the process of compiling and making deeds, he is obliged to pay attention to the applicable legal corridor, namely UUJN. However, in reality, even though a notary has carried out his duties, obligations and authority well, in the process the notary is often involved in the parties' problems. So in this case, as a form of prevention, the Notary includes a self-protection clause in the deed he makes as a form of self-protection. In this case, the formulation of the problem in this research is as follows: (1) how to implement the inclusion of a self-protection clause in notarial deeds and (2) what form of legal protection is given to notaries for clients who do not respect the notary's self-protection clause. This research is included in empirical research using a qualitative research approach. The data collection techniques are by means of interviews and also observation. The research location is at the Notary Office of Dimitri Danang Sawitrawan, S.H., M.Kn (Notary in Malang City). In this research there are the following conclusions: (1) In this case what needs to be underlined is that the Notary is not a party to the deed that the parties make before the Notary, so even if a dispute occurs between them the Notary should not be involved in any way. With the position of a Notary as such, if a Notary's deed is disputed, then the Notary's position remains not as a party or who participates or assists the parties in qualifying for Criminal Law or as a Defendant or Co-Defendant in a civil case. (2) The form of legal protection given to notaries for clients who do not comply with the notary's self-protection clause, in this case as long as the formal requirements are met and everything is in accordance with procedures, will not be a problem if the self-protection clause is not included in it. This means that in this case the deed made will not include a notary self-protection clause. However, as a form of anticipation from the notary, the notary will ask for documentation from the client as proof that everything written in the deed has been approved by the parties. The requested documentation is in the form of photos/videos and also the client's thumbprint.Keywords: Self-protection clause, notary, legal protectionE